JURNAL MANAGEMEN PROYEK INFORMATIKA ARTIFICIAL INTELLIGENCE VISION ENGINEER - Sofyan Mufti Prasetiyo; Tri Utami Ningsih; Baihaki Hakim; Arya Agung Risca Putra (CV. Multi Kreasi Media, 2022)
Artificial Intelligence Vision Engineer is a person's profession as an expert in the field of artificial intelligence. As an Artificial Intelligence Vision Engineer, they have duties and responsibilities including coordinating with data analysts, automating the devices to be used, testing and also implementing the system model being worked on, carrying out statistical analysis for company development. Artificial intelligence comes from the English